Screening Procedures for Reactive Chemicals According to the UN Manual of Tests and Criteria, Appendix 6: a Critical Review - Wim Mak; Ed De Jong (Chemical engineering transactions, 2025)
The test methods and classification criteria contained in the United Nations Manual of Tests and Criteria or UN MTC (United Nations, 2003a), currently the 8th revised edition, have become increasingly relevant in recent years as they no longer relate only to transport classification (TDG), but also to the Globally Harmonized System of Classification and Labelling of Chemicals (GHS). Where more and more new substances are placed on the market and thus need to be evaluated for their hazardous properties, the application of proper screening procedures and, if necessary, proper test methods has become even more important. An essential requirement is that such work is done by competent personnel and that clear procedures and criteria are available. This paper presents an overview of the current screening procedures and criteria and identifies and addresses some common misunderstandings and misinterpretations. It also proposes a couple of possible solutions that could lead to a better use and application of these procedures. In this way, lengthy discussions between industry and authorities as well as unnecessary testing can be avoided.